Making people meet: volunteers’ contributions to social connection for the well-being of self and others - Nina Petersen Reed; Julia Hagen (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Social isolation and loneliness are significant public health challenges that reduce well-being. The voluntary sector is suggested to be an important contributor in reducing loneliness and enhancing social connectedness and well-being in everyday life. This study aimed to contribute knowledge about how volunteers may help promote social connections and well-being, by exploring the experiences and perspectives of volunteers themselves. Methods We conducted a qualitative study in Norway interviewing nine volunteers. Data was analysed using reflexive Thematic Analysis. Findings We developed three themes: Being part of and facilitating a variety of meaningful relationships and roles, Creating spaces of trust in places of shared activity, and Calling for more diversity in volunteering while acknowledging challenges. Conclusions Volunteers’ may contribute to social connection and well-being, particularly through arranging social activities where relationships are equal and established spontaneously. Some challenges remain before volunteer activities are fully inclusive for all. Extended organizational support of volunteers may be necessary for recruitment and continuity of volunteer efforts towards some marginalized groups.